ANALYSIS OF DELAYS IN DELIVERY OF EXPORTED GOODS USING THE SIX SIGMA METHOD IN FURNITURE COMPANIES - Dama Yuninata; Dian Nur Ikayanti (Jurnal Manajemen Bisnis dan Terapan, 2025)
The background of this research was the discovery during a field study that there were problems in the delivery process at Sentana Rattan Furniture, namely delays in delivery which could affect service quality. The purpose of this study is to identify the types of delivery delay problems that often occur, the factors that cause delivery delays, and improvement strategies to reduce delivery delays. The data analysis method used in this study is the six sigma method with the DMAIC (Define, Measure, Analyze, Improve, Control) stages. The results of this study note that the problem of late delivery that occurs is raw materials, factors causing delays in delivery are unavailability of raw materials in warehouses, employees who are less focused, employees do not enter simultaneously, lack of ship space, lack of maintenance of the trucking fleet, changes in weather uncertain. The improvement strategy to reduce delivery delays is to manage raw material inventory properly and increase coorperation with other raw material suppliers, the workforce must focus, make strict regulations, maintain communication with shipping companies, carry out periodic maintenance of the trucking fleet, and maintain communication with buyers. Control of delivery delays is caried out using the standard operational procedure (SOP).